Real-virtual Monte Carlo simulation on impulse-momentum and collisions - Wartono Wartono; Dwi Hartoyo; Nilasari Nilasari; John Rafafy Batlolona (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This study aims to determine the differences in scientific literacy of students who were given inquiry learning through a real-virtual Monte Carlo experiment with students who were given conventional learning. This study used quasi experimental design with pretest-posttest control group. The results showed that the ability of students who were taught by inquiry learning models through real-virtual Monte Carlo experiments had higher scientific literacy than those taught with conventional models, it also applied well to students with high and low initial abilities. The results of the average gain in scientific literacy scores also showed a higher value between students who studied with the inquiry model through a real-virtual Monte Carlo experiment with students who studied with conventional models. The novelty of this research is combining real and virtual activities become real-virtual Monte Carlo by using the inquiry learning model to improve students' scientific literacy.